2018
DOI: 10.1111/nep.13070
|View full text |Cite
|
Sign up to set email alerts
|

iConnect CKD – virtual medical consulting: A web‐based chronic kidney disease, hypertension and diabetes integrated care program

Abstract: The programme demonstrated safe, expedited and efficient follow up with a clinical and web based programme. Support from the general practitioners and patients was encouraging, despite logistical issues. Ongoing evaluation of VC services will continue and feasibility to larger networks and more chronic diseases remains the long term goal.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
54
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 50 publications
(54 citation statements)
references
References 16 publications
0
54
0
Order By: Relevance
“…More than half of the included studies were from 1 of 2 settings: 26 from the Champlain BASE program and 13 from VA settings. 7,[37][38][39][40][41][42][43][44][45][46][47][48] Of the remaining 24 studies, there were 12 from community health centers or large public health care systems, 43,[49][50][51][52][53][54][55][56][57][58][59] 8 from academic medical centers, [60][61][62][63][64][65][66][67] 2 from a nongovernmental humanitarian organization, 68, 69 1 from a not-for-profit integrated health care delivery system, 70 and 1 from a private company providing e-consult services. 71 Most studies were observational in design and lacked a control group.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…More than half of the included studies were from 1 of 2 settings: 26 from the Champlain BASE program and 13 from VA settings. 7,[37][38][39][40][41][42][43][44][45][46][47][48] Of the remaining 24 studies, there were 12 from community health centers or large public health care systems, 43,[49][50][51][52][53][54][55][56][57][58][59] 8 from academic medical centers, [60][61][62][63][64][65][66][67] 2 from a nongovernmental humanitarian organization, 68, 69 1 from a not-for-profit integrated health care delivery system, 70 and 1 from a private company providing e-consult services. 71 Most studies were observational in design and lacked a control group.…”
Section: Methodsmentioning
confidence: 99%
“…71 Most studies were observational in design and lacked a control group. One study reported data from a pilot randomized controlled trial; 53 3 studies reported results from cluster randomized controlled trials; 49,56,70 3 studies were pre-post evaluations with a comparison group; 62,66,72 and 1 study employed a retrospective cohort design with a comparison group. 48 Most results were positive.…”
Section: Methodsmentioning
confidence: 99%
“…exploring issues of usability and acceptability). 45,[99][100][101][102][103][104][105][106][107][108][109][110][111][112][113] Many focus specifically on the clinical use of Skype, 91,[114][115][116][117][118][119][120][121][122][123] either on its own or in combination with other technologies [e.g. WhatsApp (WhatsApp Inc., Mountain View, CA, USA) messaging 124 or FaceTime 125,126 ].…”
Section: Evidence Relating To the Use Of Virtual Consultationsmentioning
confidence: 99%
“…Randomized controlled trials have shown such consultations to be acceptable, safe and effective (and, when measured, to reduce patient-borne costs) in patients deemed clinically eligible in a range of conditions including adult and teenage diabetes [16][17][18], chronic kidney disease [19], chronic obstructive pulmonary disease [20,21], mental health conditions [22,23], chronic pain [24][25][26], support after premature birth [27], support of patients in care homes [28], post-operative follow-up for orthopedics [29][30][31][32], plastic surgery [33] and prostate cancer [34].…”
Section: Introduction Backgroundmentioning
confidence: 99%